Efficacy of 15N-nitrogen in fertilization of pea mixtures with wheat, barley, and oats - A. Rutkowska; D. Pikuła (Plant, Soil and Environment, 2016)
The effect of mineral nitrogen (N) nutrition on seed production and acquisition of 15N from fertilizers by components of cereal-pea mixtures was investigated. Yields of wheat-pea and oats-pea mixtures raised together with the increase of cereals percentage in the pot, and higher seed yields of mixture with barley was affected by a larger share of pea plants. The percentage of nitrogen derived from fertilizers was significantly higher in cereals as compared with pea. Pea accumulated the greatest quantity of nitrogen from fertilizers in straw and roots, and cereals translocated 15N mainly to ears - grain and glumes with rachis. The percentage of 15N in seeds of pea amounted to 15% on the average, and in grain of cereals - 54% to 60% of the total N taken up.